(untitled) (Physical Education, Health and Social Sciences, 2025)
People who spend a lot of time sitting and reading or using a computer frequently develop forward head posture. The weight of the head is kept in front of gravity in a forward head position, shortening the sub occipital muscles and lengthening the pre- vertebral muscles, which increases the flexion moment of the spine. Increased neck discomfort, headaches, temporomandibular (jaw) joint dysfunction, and limited neck mobility are all linked to forward head position. The objective of this study is to evaluate the prevalence of forward head posture in students and young adults and to assess the risk factors of forward head posture. The craniovertebral angle is the most widely used measurement for assessing forward head posture. Subjects are included and excluded according to the criteria developed. Measurement of the craniovertebral angle is usually performed with the help of photometric way and with the help of goniometer. A self-made questionnaire is formed to identify the risk factors. Forward head posture and the magnitude of the craniovertebral angle are inversely related. Data showed that out of 370 participants 267 students have forward head posture while the remaining 103 have not. Those who have forward head posture also find in the activity like reading books in abnormal posture, playing electronic gadgets while bending their head and carrying a heavy bag pack. Prevalence of forward head posture is found to be 72.2% among the students with the age between 12-16. Forward Head Posture is found more prevalent in boys than girls.